Sustainable Urban Development in Malaysia: Enhancing Green Roofs with Integrated Technologies - Tang, Yien Yu; Slimani, Youcef; Al-Ghazal, Mukhtar Ali; Talukdar, Gaurav; Maharjan, Amit Kumar (Tecno Scientifica Publishing & Society of Tropical Science and Technology, 2023)
Urbanization and population density surges globally have triggered environmental challenges, with the construction sector notably contributing to greenhouse gas emissions and high energy consumption. Urban expansion has exacerbated issues, converting green spaces into impermeable structures and heightening flood risks. Green roofs have emerged as an eco-friendly solution, excelling in stormwater management, mitigating the urban heat island effect, enhancing air quality, reducing noise transmission, preserving biodiversity, extending roof lifespan, and augmenting aesthetics. They absorb rainwater, decreasing stormwater runoff, yet entail higher installation and maintenance costs and potential fire hazards compared to conventional roofs. In Malaysia, government policies and incentives drive green roof adoption, particularly in residential, commercial, and institutional buildings, predominantly of the intensive green roof type. Buildings undergo green rating tool evaluations for green certification. Despite progress, challenges persist, including expertise shortages, lack of design guidelines, limited research, low public awareness, and green roof component disposal issues. Addressing these demands significant government efforts, including robust policy development, increased support for local companies, expanded research initiatives, heightened public awareness, and optimized synergy with other technologies. Integrating green roofs with solar panels and utilizing greywater for irrigation can reduce energy and water consumption concurrently, showcasing potential for comprehensive and sustainable urban development.